Finite element modeling of the puncture-cutting response of soft material by a pointed blade. (September 2019) - Gzaiel, Marwa; Triki, Ennouri; Barkaoui, Abdelwahed
Highlights: FE modeling of the combined puncture-cutting of soft membranes by pointed blades. FE model aimed to propose an energy-based method. Predicted values of energies match well with experimental data. Determining the stress state during the insertion process of the pointed blade. Stress field analysis showed a mixed fracture mode. Abstract: Finite element analysis of combined puncture and cutting of a soft substrate by pointed blades allows further progress in investigating material failure properties, as well as in determining the stress state during the insertion process of the pointed blade. In the current work, a finite element model of the puncture-cutting test was developed using ABAQUS explicit scheme, assuming a non-linear hyperelastic neoprene rubber-like material. Based on the phenomenological model of Mooney-Rivlin, this study suggests an energy-based method, which was derived from both the curve of the puncture cutting force and the pointed blade displacement. The required energy was computed from the work variation as a function of the occurred fracture surface area. The obtained results revealed that finite element analysis was able to accurately predict the material resistance to a combined puncture and cutting motion. Moreover, the stress field analysis showed that the puncture cutting of soft substrates involved a combined stress state, generating then a mixed fracture mode. Graphical abstract: Image, graphical abstract